(untitled) (Itinera, 2018)
In this article we intend to analyze some of the aspects that promote a comparison between Pier Paolo Pasolini and Friedrich Nietzsche. Our purpose is to examine the texts with the aim of deducing the traits of the "double life" of the outdated philosopher in face of his own time. Far from wanting to be exhaustive, however, we chose two figures which present emblematic characteristics of this relation. We will focus on two key questions: 1) The sense of out-datedness felt by the two authors 2) The tendency to self-contradiction inspired by their need for authenticity.